Model Manajemen Resiko dalam Penyelenggaraan Layanan Pendidikan - Rahma Fitri Wahyuni (CV. ITTC INDONESIA, 2025)
Integrated Education, specifically designed to address the widespread challenges associated with implementing Risk Management in educational institutions, which often operate in a reactive and compliance-oriented manner. The method applied in this study is a detailed descriptive-conceptual analysis, comparing established global Risk Management standards with the very specific strategic and operational context of higher education institutions. The resulting model is fundamentally based on a paradigm shift from simple compliance to active risk performance, using a structure framed by four critical Strategic Risk Pillars: Academic, Financial, Technology, and Reputation. The study's key finding is the establishment of a mandatory and dynamic Integration and Feedback mechanism. This mechanism ensures that all Mitigation Action Plans are explicitly and formally linked to the Annual Work Plan and Budget to secure the necessary resource allocation, while the effectiveness of all mitigation efforts is continuously monitored and measured directly through the achievement of Key Performance Indicators. Most importantly, failure to achieve Key Performance Indicator targets automatically triggers a feedback loop for a comprehensive revision of the institutional risk profile. Ultimately, this robust framework effectively transforms MR from a passive regulatory obligation into a proactive strategic performance driver, thereby significantly enhancing the overall resilience of the organization and consistently ensuring continuous quality improvemen.